The Different Effect of PBL, Inquiry, and DI on the Problem-Solving Skill in Science - Rina Ning Tyas; Mundilarto Mundilarto (Journal of Science Education Research, 2019)
The purposes of this study were: (1) to analyze the different effect of PBL, inquiry, and DI on the problem-solving skill in science of the students; (2) to analyze the different effect of PBL and inquiry on the problem-solving skill in science of the students; (3) to analyze the different effect of PBL and DI on the problem-solving skill in science of the students; and (4) to analyze the different effect of inquiry and DI on the problem solving skill in science of the students. This research was a quasi-experiment with the problem-solving skill as the dependent variable, learning model (PBL, inquiry learning, and DI) as the independent variable, and prior knowledge as the covariance variable. The population of this research was grade VIII students of SMP N 1 Batang and the sample was three groups established using the cluster random sampling technique. The results of this study showed: (1) there is a different effect of PBL, inquiry, and DI on the problem-solving skill in science of the students; (2) there is no different effect of PBL and inquiry on the problem-solving skill in science of the students; (3) there is a different effect of PBL and DI on the problem solving skill in science of the students; and (4) there is a different effect of inquiry and DI on the problem solving skill in science of the students.